(untitled) (International Journal of Food and Nutritional Sciences, 2023)
An experiment has been conducted at the Agricultural Research Field of Department of Genetics and Plant Breeding, Rama University, Kanpur, during Kharif session 2023, understand the pattern of genetic variability and heritability through the investigation of 24 mung bean genotypes including checks. The study reveals diverse traits among mung bean genotypes. The Days to 50 flowering (DFF) range from 49.333 to 53.333 days, with some genotypes, like IPM 02 - 03, flowering earlier, and others, like NM - 1 (Dull), later. Plant heights (PH) vary from 50.999 to 95.667 centimetres, with IPM 302 - 2 exhibiting taller plants and China Mung - 2 shorter ones. Primary branches per plant (PB) range from 1.900 to 4.067, with IPM 205 - 7 having fewer and EC 496839 more branches. Secondary branches per plant (SB) vary from 5.667 to 10.000, with IPM 205 - 7 having fewer and NM - 1 (Dull) more branches. Cluster count per plant ranges from 5.600 to 10.933, with China Mung - 2 having fewer and BDY - R2 more clusters. Pod count per plant ranges from 12.433 to 31.533, with IPM 02 - 03 having fewer and Choti Mung - 1 more pods. Days to maturity (DM) vary from 67.000 to 86.000 days. Pod length (PL) ranges from 6.533 to 9.400 centimetres. Seeds per pod (SP) vary from 2.577 to 8.713, and 100-seed weight (SW) ranges from 2.577 to 16.840 grams. Seed yield per plant (SY) varies from 8.607 to 16.840 grams. Biological yield (BY) ranges from 37.667 to 55.000 kg/ha, and Harvest Index (HI) from 18.300% to 37.767%. These findings offer insights into mung bean diversity, aiding breeding and cultivation strategies for enhanced productivity and resource efficiency. The genotypic correlation matrix for mungbean traits highlights key relationships: early flowering correlates with faster maturity and higher seed counts per pod, taller plants tend to have more primary branches but fewer secondary branches and lower seed yields, and a higher number of pods per plant significantly contributes to overall harvestable yield.